2009
DOI: 10.1007/s10059-009-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Pathogenesis of Murine Gammaherpesvirus 68 Infection of the Central Nervous System

Abstract: Gammaherpesvirus infection of the central nervous system (CNS) has been linked to various neurological diseases, including meningitis, encephalitis, and multiple sclerosis. However, little is known about the interactions between the virus and the CNS in vitro or in vivo. Murine gammaherpesvirus 68 (MHV-68 or (gamma)HV-68) is genetically related and biologically similar to human gammaherpesviruses, thereby providing a tractable animal model system in which to study both viral pathogenesis and replication. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Both over-stimulation and attenuated expression of pro-inflammatory cytokines in suckling or weanling mice have been associated with poor disease outcome [10,29,177]. Likewise, differences in the function of immune cells between animals of different ages can influence the development of viral disease [59].…”
Section: The Role Of Age In the Susceptibility Of Mice To Flaviviral mentioning
confidence: 99%
“…Both over-stimulation and attenuated expression of pro-inflammatory cytokines in suckling or weanling mice have been associated with poor disease outcome [10,29,177]. Likewise, differences in the function of immune cells between animals of different ages can influence the development of viral disease [59].…”
Section: The Role Of Age In the Susceptibility Of Mice To Flaviviral mentioning
confidence: 99%
“…Lytic gene expression, DNA replication, and virion production were concomitantly induced after treatment with TPA and sodium butyrate, but they were blocked after treatment with GCV. Taken together, these results suggest that both productive and latent infections may be established in neuroblastoma cells, which may account for persistent infection in the brain of infected mice (Cho et al, 2009;Kang et al, 2012). Because only few cell lines are available to study persistent infection of MHV-68 áå= îáíêç following ÇÉ= åçîç infection, MHV-68 infection in neuroblastoma cells may provide a valuable experimental system to investigate the various aspects of γHV latency by using functional genomics.…”
Section: Induction Of Mhv-68 Productive Replication In Persistently Imentioning
confidence: 96%
“…EBV infection has been linked to various neurological diseases such as aseptic meningitis, encephalitis, human immunodeficiency virus (HIV)-related primary central nervous system (CNS) lymphoma, and multiple sclerosis (MS) (Bossolasco et al, 2006;Said et al, 1997;Serafini et al, 2007). Consistent with the neurological pathogenesis of human gammaherpesvirus (γHV), murine gammaherpesvirus-68 (MHV-68 or also called γHV-68; a murine homolog of EBV) has also been reported to infect the brain and replicate in it as well as in various cell types derived from the CNS (Cho et al, 2009;Terry et al, 2000). Furthermore, our recent studies by noninvasive bioluminescence imaging of a Virus-Host Interactions Laboratory, Division of Biotechnology, Department of Biosystems and Biotechnology, College of Life Sciences and Biotechnology, Korea University, Seoul 136-713, Korea *Correspondence: moonsong@korea.ac.kr recombinant MHV-68 expressing the firefly luciferase (M3FL) suggested that MHV-68 may persist in the brain following cerebral infection .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations